Real-Time Data Connectivity to Deep Autonomous Seafloor Instrumentation in Adverse Flow Conditions - Christopher Ewert; Romain Heux; Noah Howins; Matthias Lankhorst; Gaston Manta Dominguez; Uwe Send (Oceanography, 2025)

Predicting the Loop Current dynamics combining altimetry and deep flow measurements through the Yucatan Channel - Gaston Manta; Giovanni Durante; Julio Candela; Uwe Send; Julio Sheinbaum; Matthias Lankhorst; Rémi Laxenaire (Frontiers in Marine Science, 2023)
The Loop Current is the main mesoscale feature of the Gulf of Mexico oceanic circulation. With peak velocities above 1.5 m s –1 , the Loop Current and its mesoscale eddies are of interest to fisheries, hurricane prediction and of special concern for the security of oil rig operations in the Gulf of Mexico, and therefore understanding their predictability is not only of scientific interest but also a major environmental security issue. Combining altimetric data and an eddy detection algorithm with 8 years of deep flow measurements through the Yucatan Channel, we developed a predictive model for the Loop Current extension in the following month that explains 74% of its variability. We also show that 4 clusters of velocity anomalies in the Yucatan Channel represent the Loop Current dynamics. A dipole with positive and negative anomalies towards the western side of the Channel represents the growing and retracted phases respectively, and two tripole shape clusters represent the transition phases, the one with negative anomalies in the center associated with 50% of the eddy separation events. The transition between these clusters is not equally probable, therefore adding predictability. Finally, we show that eddy separation probability begins when the Loop Current extends over 1800 km (~27.2°N), and over 2200 km of extension, eddy detachment and reattachment is more frequent than separation. These results represent a step forward towards having the best possible operational Loop Current forecast in the near future, incorporating near real-time data transmission of deep flow measurements and high resolution altimetric data.

Atlantic Meridional Overturning Circulation: Observed Transport and Variability - Eleanor Frajka-Williams; Isabelle J. Ansorge; Johanna Baehr; Harry L. Bryden; Maria Paz Chidichimo; Stuart A. Cunningham; Gokhan Danabasoglu; Shenfu Dong; Kathleen A. Donohue; Shane Elipot; Patrick Heimbach; N. Penny Holliday; et al. (Frontiers in Marine Science, 2019)

An undercurrent off the east coast of Sri Lanka - Arachaporn Anutaliya; Uwe Send; Julie L. McClean; Janet Sprintall; Luc Rainville; Craig M. Lee; S. U. Priyantha Jinadasa; Alan J. Wallcraft; E. Joseph Metzger (Ocean Science, 2017)
The existence of a seasonally varying undercurrent along 8° N off the east coast of Sri Lanka is inferred from shipboard hydrography, Argo floats, glider measurements, and two ocean general circulation model simulations. Together, they reveal an undercurrent below 100–200 m flowing in the opposite direction to the surface current, which is most pronounced during boreal spring and summer and switches direction between these two seasons. The volume transport of the undercurrent (200–1000 m layer) can be more than 10 Sv in either direction, exceeding the transport of 1–6 Sv carried by the surface current (0–200 m layer). The undercurrent transports relatively fresher water southward during spring, while it advects more saline water northward along the east coast of Sri Lanka during summer. Although the undercurrent is potentially a pathway of salt exchange between the Arabian Sea and the Bay of Bengal, the observations and the ocean general circulation models suggest that the salinity contrast between seasons and between the boundary current and interior is less than 0.09 in the subsurface layer, suggesting a small salt transport by the undercurrent of less than 4 % of the salinity deficit in the Bay of Bengal.

Collaborative Observations of Boundary Currents, Water Mass Variability, and Monsoon Response in the Southern Bay of Bengal - Craig Lee; S.U.P. Jinadasa; Arachaporn Anutaliya; Luca Centurioni; Harinda Fernando; Verena Hormann; Matthias Lankhorst; Luc Rainville; Uwe Send; Hemantha Wijesekera (Oceanography, 2016)

Autonomous Ocean Measurements in the California Current Ecosystem - Mark Ohman; Daniel Rudnick; Alexander Chekalyuk; Russ Davis; Richard Feely; Mati Kahru; Hey-Jin Kim; Michael Landry; Todd Martz; Christopher Sabine; Uwe Send (Oceanography, 2013)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

Spatial and temporal structure of the Denmark Strait Overflow revealed by acoustic observations - Andreas Macrander; Rolf H. Käse; Uwe Send; Héðinn Valdimarsson; Steingrímur Jónsson (Ocean Dynamics, 2007)